PEDAGOGICAL POTENTIAL OF A PICTURE TO ENHANCE SPEECH FOR CHILDREN WITH LANGUAGE DISORDERS - Kerevica, Jekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The scientist A. Leontyev assures that the language competence is the result of development of continuous use of each language. Only through active communication and active speech activity an understanding about language emerges for the child (Leontyev, 1977). The scientist Glukhov (2005) outlines the skill to improve the language abilities by performing the speech activity in the process of communication. Whereas, one of the most significant factors in the process of mastering the language is a positive emotional background, where the child is encouraged to perceive visible, apparent things, living beings, natural phenomena, to listen and pronounce words which designate them. This also inspires to investigate the pedagogical potential of a picture to enhance speech for children with language disorders.The picture is a significant visual aid for a child not only to be taught but also to have fun for improving the language skills. Therefore, it is worked out a set of pictures as a help for the parents to work with a child at home. In a such way a speech therapist is involving the parents in a teaching process to prolong an educational process with a child. As a result, the parents get a pedagogic experience and the efficient development for a child language.